Endodontists’ Self-Assessment about Pharmacological Strategies for Management of Endodontic Pain - Letycia Accioly Simões Coelho; Marcos Dezotti Luiz; Artur Villas Bôas Weckwerth; Rodrigo Ricci Vivan; Marco Antônio Hungaro Duarte; Murilo Priori Alcalde; Paulo César Rodrigues Conti; Yuri Martins Costa; Leonardo Rigoldi Bonjardim (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To assess the pharmacological strategies of a group of Brazilian endodontists regarding endodontic pain. Material and Methods: Specialists answered a questionnaire with two main themes: 1) Pharmacological prescription patterns and 2) Endodontic procedures and risk of postoperative pain. The collective data were presented as descriptive statistics. Results: Almost all endodontists reported using drugs for pain management, mainly for apical abscess (65.8%) and irreversible pulpitis (61%), as well as more after (59.6%) than before (23.3%) endodontic procedure. Dipyrone (72.6%) and ibuprofen (56.8%) were the most  prescribed systemic drugs. The most used local anesthetics were mepivacaine (58.2%) and articaine (57.5%). When necessary, 74.7% of specialists use supplementary anesthesia with an additional technique. Extravasation of filling materials (81.5%), limit of apical obturation (71.2%), and instrumentation (66.4%) 1 mm beyond were the main endodontic procedures to increase the risk of postoperative pain. Conclusion: While most strategies employed by Brazilian Society of Endodontics members are evidence-based, divergences in responses highlight the need for further research. This underscores the importance of more profound insights and potential standardization in pain management strategies among professionals.